Ecological and demographic impacts of a recent volcanic eruption on two endemic patagonian rodents - Lacey, Eileen Anne (2019)
Catastrophic events can significantly impact the demographic processes that shape natural populations of organisms. However, linking the outcomes of such events to specific demographic parameters is often challenging due to a lack of detailed pre-event data. The eruption of the Puyehue-Cordon Caulle volcanic complex on 4 June 2011 had profound consequences for the biota of southwestern Argentina. Our long-term behavioral, ecological, and demographic studies of two species of tuco-tucos (Ctenomys sociabilis and C. haigi) that occur in the region most heavily impacted by ash fall from the eruption provided an unusual opportunity to assess the effects of this event on natural populations of mammals. The post-eruption density of the study population for each species was markedly reduced compared to pre-eruption values, with the relative magnitude of this reduction being greater for the group-living C. sociabilis. The more extensive data set for this species indicated that ash fall from the eruption altered the food resources available to these animals; differences in pre- and post-eruption stable isotope signatures for fur samples from C. sociabilis were consistent with observed changes in vegetation. Per capita female reproductive success was also reduced in this species during the first breeding season following the eruption. Based on our detailed demographic records for C. sociabilis, neither survival of yearling females from 2010 to 2011 nor the percentage of unmarked females in the study population in 2011 differed from pre-eruption values. Instead, the post-eruption decrease in population density for C. sociabilis appeared to reflect reduced within-population recruitment of juvenile females to the 2011 breeding population. Although the eruption did not result in the local extinction of either study population, the demographic consequences detected are likely to have impacted the effective sizes of these populations, creating important opportunities to link specific demographic parameters to previously reported decreases in genetic variability detected after this significant natural event.